The Association of Medications and Vaccination with Risk of Pneumonia in Inflammatory Bowel Disease. Issue 6 (27th August 2019) - Gregory, Martin H; Ciorba, Matthew A; Wiitala, Wyndy L; Stidham, Ryan W; Higgins, Peter; Morley, S Celeste; Hou, Jason K; Feagins, Linda A; Govani, Shail M; Cohen-Mekelburg, Shirley A; Waljee, Akbar K
Abstract: Background: Patients with inflammatory bowel disease (IBD) are at increased risk for pneumonia, and corticosteroids are reported to amplify this risk. Less is known about the impact of corticosteroid-sparing IBD therapies on pneumonia risk or the efficacy of pneumococcal vaccination in reducing all-cause pneumonia in real-world IBD cohorts. Methods: We performed a population-based study using an established Veterans Health Administration cohort of 29, 957 IBD patients. We identified all patients who developed bacterial pneumonia. Cox survival analysis was used to determine the association of corticosteroids at study entry and as a time-varying covariate, corticosteroid-sparing agents (immunomodulators and antitumor necrosis-alpha [TNF] inhibitors), and pneumococcal vaccination with the development of all-cause pneumonia. Results: Patients with IBD who received corticosteroids had a greater risk of pneumonia when controlling for age, gender, and comorbidities (hazard ratio [HR] 2.21; 95% confidence interval [CI], 1.90–2.57 for prior use; HR = 3.42; 95% CI, 2.92–4.01 for use during follow-up). Anti-TNF inhibitors (HR 1.52; 95% CI, 1.02–2.26), but not immunomodulators (HR 0.91; 95% CI, 0.77–1.07), were associated with a small increase in pneumonia. A history of pneumonia was strongly associated with subsequent pneumonia (HR = 4.41; 95% CI, 3.70–5.27). Less than 15% of patients were vaccinated against pneumococcus, and this was not associated with a reduced risk of pneumonia (HR = 1.02; 95% CI, 0.80–1.30) in this cohort. Conclusion: In a large US cohort, corticosteroids were confirmed to increase pneumonia risk. Tumor necrosis-alpha inhibitors were associated with a smaller increase in the risk of pneumonia. Surprisingly, pneumococcal vaccination did not reduce all-cause pneumonia in this population, though few patients were vaccinated.